2024
DOI: 10.3389/fphar.2023.1300310
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliprenin via increase in the MECP2 and attenuation of oxidative stress mitigates the autistic-like behaviors in mouse model of maternal separation stress

Parnian Karimi,
Mehryar Shahgholian Ghahfarroki,
Zahra Lorigooini
et al.

Abstract: Introduction: Autism spectrum disorder (ASD) is a complex neurodevelopmental condition. Maternal separation (MS) stress is an early-life stress factor associated with behaviors resembling Autism. Both MECP2 and oxidative stress are implicated in the pathophysiology of Autism. Umbelliprenin (UMB) is a coumarin compound with various pharmacological properties. Our study aimed to investigate the potential effects of UMB in mitigating autistic-like behaviors in a mouse model subjected to MS stress, focusing on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Regarding DNA methylation, several signatures and patterns are found in specific genomic regions impacting gene expression related to synaptic function, neuronal signaling, and brain development and maturation. Hence, methylation of newly discovered genes, like the oxytocin receptor (OXTR), methyl-CpG-binding protein 2 (MECP2), Reelin (RELN), and BDNF, have been linked to ASD pathophysiology [161][162][163][164].…”
Section: Epigenetic Mechanisms In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding DNA methylation, several signatures and patterns are found in specific genomic regions impacting gene expression related to synaptic function, neuronal signaling, and brain development and maturation. Hence, methylation of newly discovered genes, like the oxytocin receptor (OXTR), methyl-CpG-binding protein 2 (MECP2), Reelin (RELN), and BDNF, have been linked to ASD pathophysiology [161][162][163][164].…”
Section: Epigenetic Mechanisms In Asdmentioning
confidence: 99%
“…Epigenetic manipulation of this gene can, in fact, cause abnormal behaviors like those seen in ASD. A cohort study of patients with ASD revealed significantly increased levels of MECP2 methylation compared to controls in specific CpG islands [164]. Moreover, locus-specific methylation at the MECP2 promoter was positively correlated with the development of ASD-like symptoms such as increased repetitive behaviors, anxiety, and impaired social interactions [165].…”
Section: Epigenetic Mechanisms In Asdmentioning
confidence: 99%